A Guideline on How to do Market Research for Branding Purposes at Maru Design Agency - Richard Kurniawan (Institute of Research and Community Outreach - Petra Christian University, 2020)
This is a final project report on a problem at maru design agency. Maru design is a strategic and brand design agency which provides company with their services of branding and rebranding. The services help their client to create and develop brands and solve the company’s. Their services need to research about the product of the client’s brand or prospect’s brand, but there is no clear procedure to do market research even though it is important step to attract prospect and before they develop the brand. Thus, marketing research guideline is needed for maru design. Guideline is used as procedures by which to determine a course of action. The guideline will consist of prospect’s information, product analysis, customer analysis, and competitor analysis to provide a detailed data and information. Thus, this guideline will help to do in-depth market research for any people from any background and improve maru design. Keywords: Market research guideline, Market Research, Guideline, Branding